Removal of toluene vapour using agro-waste as biofilter media - Singh R.S.; Agnihotri S.S.; Upadhyay S.N. (My University, 2025)
Biodegradation of toluene vapour was investigated in a laboratory scale biofilter packed with cylindrical pieces of yellow-gram (Cajanus cajan) stalk. Inlet concentrations and volumetric flow rates of toluene were varied from 2.56 to 34.73 g/m3 and 0.18 to 0.24 m3/h, respectively. The steady state was achieved within seven days and the degradation of toluene followed an exponential behaviour with time. Elimination capacity increased and tended towards a constant value but removal efficiency decreased with increase in inlet toluene loading. Depending upon loading rate, the process was either mass transfer or reaction-controlled. © 2005 Elsevier Ltd. All rights reserved.